China's rhetoric and soft power towards the Portuguese-speaking countries : the case of Angola - Tavares Martins, Nuno (2014)
The thesis analyses China’s foreign policy towards the Portuguese-speaking countries, particularly the case of Angola. The People’s Republic of China has been putting great emphasis on the relations with other developing countries. The eight Portuguese-speaking countries, Angola, Brazil, Cabo Verde, Guinea-Bissau, Mozambique, Portugal, São Tomé and Príncipe and Timor-Leste constitute a group with a population of around 250 million people, a vast wealth of natural resources and potential for gaining economic and political importance in the near future. The way China frames its rhetorical communication and establishes relationships must be understood to provide a perspective on its foreign policy. Political communication involves a ritual with a rhetor, a message and an audience. This phenomenon and the resulting interaction need to be approached from a political perspective in order to understand the dynamics of communication and power. The theoretical framework consists of using rhetorical criticism to analyse the speeches made by the Chinese and Angolan representatives at the Forum for Economic and Trade Cooperation between China and the Portuguese-speaking Countries (Forum Macao) in 2003 and 2006 as well as China’s African Policy official document. Roderick P. Hart and Sonja K. Foss describe models that serve as guides for rhetorical criticism. One of the most useful models to perform a rhetorical analysis is Kenneth Burke’s dramatistic theory and its concepts: the pentad, hierarchy, identification, and the guilt, purification and redemption cycle. As for the power component, Chinese diplomacy is using what is labelled in the specialized terminology as soft power. It focus more on the power of attraction and it is a term devised in 1990 by Professor Joseph S. Nye. It is thought-provoking to analyse how political argumentation is constructed to present political messages. In this thesis, Chinese rhetoric and its soft power actions will be explored to understand the relationship with Angola. Thus, rhetorical criticism and soft power provide a framework to analyse which aspects are either emphasised or neglected in the official rhetoric. These tools are essential to understand what has happened and what is happening. In addition, one might be able to gain a wider knowledge on the role that China can play vis-à-vis the other developing countries: a development partner, an economic competitor or a coloniser.